Mann-Kendall Mutation Analysis of Temporal Variation of Apparent Stress in Qinba Mountains and Its Adjacent Areas. Issue 1 (February 2021) - Wang, Weidong; Yi, Zheng; Chen, Dou
Abstract: In this abstract, we use the Mann-Kendall Mutation analysis to determine the source parameters of 125 earthquakes in the Qinba Mountains and its neighboring areas between 1997 and 2013. Seismic moments, apparent stress, and seismic radiant energy of the earthquakes were calculated. The Mann-Kendall mutation test was used to analyze the temporal data of the apparent stress. The results indicate that there occurred three downward mutation points in apparent stress in June 1998, October 1998 and March 1999, and then only one earthquake, Wudu 4.5earthquake with magnitude greater than 4 occurred in this area till September 2001. The average apparent stress decreases from 0.16 MPa from July 1997 to March 1999 to 0.15 MPa from April 1999 to September 2001. After the rising mutation point in apparent stress in October 2001, the average apparent stress increases from 0.15 MPa from April 1999 to September 2001 to 0.18 MPa from October 2001 to December 2013. A series of moderate to strong earthquakes with ML4.9, ML6.0, ML5.9, and ML5.2 then occurred in April 2003, May 2008, July 2008 and September 2009. The results demonstrate that the Mann-Kendall mutation analysis can fairly reflect the trend of apparent seismic stress, which is helpful for seismic activity prediction.